1981
DOI: 10.1097/00000658-198102000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis with a Palpable Mass

Abstract: Forty-two patients with abdominal masses caused by appendicitis underwent immediate surgery. A clear separation between a phlegmon and abscess could not be made before operation. In most patients, it was possible to perform an appendectomy and, thus, obviate the need for appendectomy at a subsequent admission. There were no deaths in this series of patients. The complication rate of 35.7% could have been reduced by leaving the skin wounds open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 1 publication
4
73
0
1
Order By: Relevance
“…Nonetheless, several previous studies reported high success rates of 76 to 97 % and a low incidence of postoperative complications after conservative management of patients with appendicitis associated with Fig. 1 Outcomes of patients with acute pediatric perforated appendicitis with abscess abscess [3,[8][9][10][11]. In our series, the success rate of 87.5 % without postoperative complications is consistent with those of previously published reports and appendicitis recurrence occurred in two patients before interval appendectomy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, several previous studies reported high success rates of 76 to 97 % and a low incidence of postoperative complications after conservative management of patients with appendicitis associated with Fig. 1 Outcomes of patients with acute pediatric perforated appendicitis with abscess abscess [3,[8][9][10][11]. In our series, the success rate of 87.5 % without postoperative complications is consistent with those of previously published reports and appendicitis recurrence occurred in two patients before interval appendectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Emergency surgery in such patients has been associated with an increased risk of postoperative complications, especially wound infection [3]. In our series, although appendectomy was successfully performed in all of 15 (100 %) patients, postoperative intra-abdominal abscess was detected in 5 (33.3 %), wound infection in 6 (40 %), and small bowel obstruction in 2 (13.3 %) patients.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The definitive treatment of acute appendicitis is appendicectomy. If timely appendicectomy is not done, the patients develop a mass in the right iliac fossa (Appendicular mass) as one of the early complications [4,5]. Management of an appendicular mass is controversial with three general approaches usually employed [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] It can cause dissemination of infection, intestinal injury and fecal fistula. Kumar et al [17] reported longer operation time, higher incidence of adhesions and incision extension with more postoperative complications for early appendectomy in appendiceal mass.…”
Section: Discussionmentioning
confidence: 99%